12-HETrE, a 12-LOX oxylipin of DGLA, inhibits thrombosis via Gα(s) signaling in platelets - Yeung, Jennifer (Arterioscler Thromb Vasc Biol, 2016)
OBJECTIVE: Dietary supplementation with polyunsaturated fatty acids (PUFAs) has been widely used for primary and secondary prevention of CVD in individuals at risk; however, the cardioprotective benefits of PUFAs remain controversial due to lack of mechanistic and in vivo evidence. We present direct evidence that an omega-6 PUFA, dihomo-γ-linolenic acid (DGLA), exhibits in vivo cardioprotection through 12-lipoxygenase (12-LOX) oxidation of DGLA to its reduced oxidized lipid form, 12(S)-HETrE, inhibiting platelet activation and thrombosis. APPROACH AND RESULTS: DGLA inhibited ex vivo platelet aggregation and Rap1 activation in wild-type mice, but not in mice lacking 12-LOX expression (12-LOX(−/−)). Similarly, wild-type mice treated with DGLA were able to reduce thrombus growth (platelet and fibrin accumulation) following laser-induced injury of the arteriole of the cremaster muscle, but not 12-LOX(−/−) mice, supporting a 12-LOX requirement for mediating the inhibitory effects of DGLA on platelet-mediated thrombus formation. Platelet activation and thrombus formation were also suppressed when directly treated with 12(S)-HETrE. Importantly, two hemostatic models, tail bleeding and arteriole rupture of the cremaster muscle, showed no alteration in hemostasis following 12(S)-HETrE treatment. Finally, the mechanism for 12(S)-HETrE protection was shown to be mediated via a Gα(s)-linked GPCR pathway in human platelets. CONCLUSIONS: This study provides the first direct evidence that an omega-6 PUFA, DGLA, inhibits injury-induced thrombosis through its 12-LOX oxylipin, 12(S)-HETrE, which strongly supports the potential cardioprotective benefits of DGLA supplementation through its regulation of platelet function. Furthermore, this is the first evidence of a 12-LOX oxylipin regulating platelet function in a Gα(s)-linked GPCR-dependent manner.